The value and impact of continuing professional education in the new NHS: nurses' and managers' perspectives - Dodwell, Mahrokh (1999)
The thesis explores the application of Continuing Professional Education learning in the work place, and evaluates the factors contributing to its application to clinical practice. The research specifically reviews and assesses relevant literature and theories of adult learning and evaluation. Using existing literature, empirical research work was undertaken in three case study sites. The methodological strategies of illuminative evaluation were utilised in the study, the innovation was examined in the context of "Learning milieu" (Snyder, 1971). Observations of documentary evidence, interviews with course participants and their respective managers and pre and post course questionnaires constituted the data collection. The combination of data assisted the researcher in "illuminating" issues, significant features and problems. The research study systematically and logically investigated, unfolded and clarified issues as they arose.